Respiratory and Metabolic Effects of Active Expiration in Freely Behaving Rats - Leirão, Isabela P. [UNESP]; Katayama, Pedro L. [UNESP]; Zoccal, Daniel B. [UNESP] (Wiley, 2025)
AIM: Exposure to low oxygen (hypoxia) or high carbon dioxide levels (hypercapnia) leads to a compensatory increase in pulmonary ventilation. Among the motor changes supporting the respiratory responses is the recruitment of abdominal expiratory muscles (ABD), which can enhance expiratory airflow or alter the duration of the expiratory phase. In this study, we assessed the impact of ABD recruitment on metabolic, motor, and ventilatory parameters in unanesthetized, freely behaving animals. METHODS: Sprague-Dawley Holtzman male adult rats (n = 7) were instrumented to perform simultaneous recordings of pulmonary ventilation, body temperature, diaphragmatic and ABD activities, and O2 consumption during exposure (20-30 min) to various levels of hypoxia (12%-8% O2) and hypercapnia (3%-7% CO2). RESULTS: Hypoxia or hypercapnia exposure evoked active expiration (AE); however, ABD recruitment did not occur during the entire exposure period, displaying an intermittent profile. The occurrence of AE during hypoxia and hypercapnia conditions was linked to additional increases in tidal volume when compared to periods without ABD activity (p < 0.05) and showed no associations with changes in diaphragmatic burst amplitude. Analyses of flow-like patterns suggested that AE during hypoxia recruited expiratory reserve volume during late expiration, while under hypercapnia, it accelerated lung emptying and increased the expiratory flow peak during post-inspiration. AE was also associated with increased oxygen consumption and did not improve air convection requirement. CONCLUSION: AE enhances pulmonary ventilation during hypoxia and hypercapnia primarily by increasing tidal volume. However, this motor behavior may also affect other mechanical aspects of the respiratory system to improve alveolar ventilation and gas exchange.